Gemcitabine, dexamethasone, and cisplatin (GDP) chemotherapy with sandwiched radiotherapy in the treatment of newly diagnosed stage IE/IIE extranodal natural killer/T‐cell lymphoma, nasal type - Tian, Shu (Cancer Med, 2019)
Extranodal natural killer/T‐cell lymphoma (ENKL), nasal‐type is a rare but highly aggressive disease with poor prognosis. Optimal treatment strategies for newly diagnosed localized ENKL have not been fully defined. Here we retrospectively analyzed 72 patients with newly diagnosed stage IE/IIE ENKL treated with gemcitabine, dexamethasone, and cisplatin (GDP) regimen chemotherapy with sandwiched radiotherapy in our department between May 2012 and September 2014. After 2 cycles of GDP induction chemotherapy, the complete response rate (CRR) and overall response rate (ORR) were 30.6% (22/72) and 91.7% (66/72). After whole treatment completion, the CRR and ORR were 81.9% (59/72) and 91.7% (66/72), respectively. With a median follow‐up of 57.8 months (Interquartile Range 54.0‐64.5 months), the 5‐year progression‐free survival rate was 70.9% (95% CI, 60.1% to 81.7%), and the 5‐year overall survival rate was 72.0% (95% CI, 61.6% to 82.4%), respectively. Patients with CRR after treatment had better prognosis than their counterparts. The major adverse events were myelosuppression, liver dysfunction, gemcitabine‐related skin rash, and digestive tract toxicities. Grade 3 to 4 neutropenia and thrombocytopenia were 18.0% (13/72) and 15.3% (11/72), respectively. No treatment related deaths were observed. It is concluded that the GDP regimen with sandwiched radiotherapy was an effective and well‐tolerated treatment for newly diagnosed stage IE/IIE ENKL, nasal‐type.